Sistem Informasi Bursa Lowongan Kerja Alumni Universitas Lampung Berbasis SMS Gateway - Situmorang, Togu Christian; Yusman, Machudor; Sakethi, Dwi (Jurnal Komputasi, 2017)
Collage student who has finished his study and registered as alumni need job vacancy information in accordance with their education, majors, and Grade Point Avarage (GPA). University that support the career development of graduates, needs an information system that can convey job information to alumni. Information of vacancy job available in information system of the university gives the information that can be accessed by everyone not give the information directly to the alumni. This makes available job vacancy information not quickly known to alumni who need job vacancy information. Information System for University of Lampung’s alumni is developed using PHP programming language and GAMMU as SMS Gateway application service. This system can only be used by admin that insert the data of alumni, and information of job vacancy will be sent directly to the alumni by SMS media. Before the information was sent, system will first filter the study, course and GPA of alumni. The Alumni can also register and stop to receive job vacancy information via SMS with a specific format to the contact number used on this system. Development of this vacancy information system is so that alumni get latest vacancy information according to educational targets, majors, and alumni’s GPA. Keywords: information, jobs, sms center, sms gateway, gammu.